Assessing the Benefit-Risk Profile for Pediatric Implantable Auditory Prostheses. (September 2018) - Fisher, Laurel M.; Martinez, Amy S.; Richmond, Frances J.; Krieger, Mark D.; Wilkinson, Eric P.; Eisenberg, Laurie S.
Background/Aims: Children with congenital cochleovestibular abnormalities associated with profound hearing loss have few treatment options if cochlear implantation does not yield benefit. An alternative is the auditory brainstem implant (ABI). Regulatory authority device approvals currently include a structured benefit-risk assessment. Such an assessment, for regulatory purposes or to guide clinical decision making, has not been published, to our knowledge, for the ABI and may lead to the design of a research program that incorporates regulatory authority, family, and professional input. Methods: Much structured benefit-risk research has been conducted in the context of drug trials; here we apply this approach to device studies. A qualitative framework organized benefit (speech recognition, parent self-report measures) and risk (surgery- and device-related) information to guide the selection of candidates thought to have potential benefit from ABI. Results: Children with cochleovestibular anatomical abnormalities are challenging for appropriate assessment of candidacy for a cochlear implant or an ABI. While the research is still preliminary, children with an ABI appear to slowly obtain benefit over time. A team of professionals, including audiological, occupational, and educational therapy, affords maximum opportunity for benefit. Conclusions: Pediatric patients who have abnormal anatomy and are candidates for an implantable auditory prosthetic require an individualized, multisystems review. The qualitative benefit-risk assessment used here to characterize the condition, the medical need, potential benefits, risks, and risk management strategies has revealed the complex factors involved. After implantation, continued team support for the family during extensive postimplant therapy is needed to develop maximum auditory skill benefit.